2x-13=-7(x+7)

Simple and best practice solution for 2x-13=-7(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-13=-7(x+7) equation:


Simplifying
2x + -13 = -7(x + 7)

Reorder the terms:
-13 + 2x = -7(x + 7)

Reorder the terms:
-13 + 2x = -7(7 + x)
-13 + 2x = (7 * -7 + x * -7)
-13 + 2x = (-49 + -7x)

Solving
-13 + 2x = -49 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-13 + 2x + 7x = -49 + -7x + 7x

Combine like terms: 2x + 7x = 9x
-13 + 9x = -49 + -7x + 7x

Combine like terms: -7x + 7x = 0
-13 + 9x = -49 + 0
-13 + 9x = -49

Add '13' to each side of the equation.
-13 + 13 + 9x = -49 + 13

Combine like terms: -13 + 13 = 0
0 + 9x = -49 + 13
9x = -49 + 13

Combine like terms: -49 + 13 = -36
9x = -36

Divide each side by '9'.
x = -4

Simplifying
x = -4

See similar equations:

| 8x+4=-6+7x | | 3v=9/2 | | .25x+.15(140-x)=.19(140) | | y/4+3.2+5.2 | | 3v+6(v+2)=21 | | 13x=9x+12 | | 7(y-8)+2y=7 | | 30=6/5x | | -6u+3(u+7)=9 | | 3x-2-x=102 | | x(2x-5)+x(2x-2)=(4x+3)(x-2) | | .40x+.15(140-x)=.25(140) | | 2/3(4+3) | | 6x^4+5x^2-6=0 | | 3/8=v+6 | | (3x+4)*(3x+4)=144 | | 2q+6=5(a-3) | | 8.5x-6.96=38.08 | | 2(8x-7)=2(3+8x) | | y+1/5=-3/4 | | -0.09p-0.04(6-4p)=0.03(p-4)-0.12 | | 17x-4x+27=4x-18 | | y-1/2=-7/8 | | 8r-4r+4=7r-r | | -2x-1=-8 | | 3x+4*3x+4=144 | | 5t+11(t-2)=5t+11(2t) | | (2x^2-5x+12)+(6x^2+8x-78)= | | w-6=-9 | | (8x+3)2=27 | | 1/2x^2-1/14-3/7=0 | | 2q+6=5 |

Equations solver categories